The evolution of the mass–metallicity relation and its scatter in IllustrisTNG. Issue 4 (23rd January 2019) - Torrey, Paul; Vogelsberger, Mark; Marinacci, Federico; Pakmor, Rüdiger; Springel, Volker; Nelson, Dylan; Naiman, Jill; Pillepich, Annalisa; Genel, Shy; Weinberger, Rainer; Hernquist, Lars
ABSTRACT: The coevolution of galaxies and their metal content serves as an important test for galaxy feedback models. We analyse the distribution and evolution of metals within the IllustrisTNG simulation suite with a focus on the gas-phase mass−metallicity relation (MZR). We find that the IllustrisTNG model broadly reproduces the slope and normalization evolution of the MZR across the redshift range 0 < z < 2 and mass range 10 9 < M * /M⊙ < 10 10.5 . We make predictions for the high-redshift (2 < z < 10) metal content of galaxies which is described by a gradual decline in the normalization of the metallicity with an average high-redshift ( z > 2) evolution fit by d log( Z )/d z ≈ −0.064. Our simulations indicate that the metal retention efficiency of the interstellar medium (ISM) is low: a majority of gas-phase metals (∼85 per cent at z = 0) live outside of the ISM, either in an extended gas disc, the circumgalactic medium, or outside the halo. Nevertheless, the redshift evolution in the simulated MZR normalization is driven by the higher gas fractions of high-redshift galaxies, not by changes to the metal retention efficiency. The scatter in the simulated MZR contains a clear correlation with the gas-mass or star formation rate of the system, in agreement with the observed fundamental metallicity relation. The scatter in the MZR is driven by a competition between periods of enrichment- and accretion-dominated metallicity evolution. We expect that while the normalization of the MZR declines with redshift, the slope of the correlation between metallicity and gas-mass at fixed stellar mass is not a strong function of redshift. Our results indicate that the gas fraction dependence of 'regulator' style models allows them to simultaneously explaining the shape, redshift evolution, and existence of correlated scatter with gas fraction about the MZR.